Analysis of lipase activity of JSF7 phage - Tabassum, Tasbiha; Mohammad, Khondokar Shafin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2022.